Effects of Attribute Affirmation and Achievement Goals on High School Students' Motivation - Liu, Cheng-Hong; Huang, Po-Sheng; Yin, Xian-Rui; Chiu, Fa-Chung (Frontiers in Psychology, 2021)
Researchers have suggested that receiving attribute affirmation may increase students’ motivation to confront challenge. However, we posited that to determine whether attribute affirmation increases students’ motivation to confront a challenging task, we must consider students’ dispositional achievement goals. The participants were 171 junior high school students, randomly assigned to an attribute affirmation or no affirmation condition. The results showed that attribute affirmation enhanced the tendency to confront a challenging task for students who endorsed low mastery-approach and low performance-approach goals simultaneously (b = 0.5, p = .015). The effect was mainly mediated by the increasing state performance-approach goals in confronting the task (indirect effect = 0.21, 95% CI = 0.04 to 0.49). However, being attribute-affirmed decreased the tendency to confront the challenging task for students adopting a dominant performance-approach goal orientation (b = -0.76, p = .049). In addition, for students adopting a dominant mastery-approach goal orientation or adopting high mastery-approach and high performance-approach goals simultaneously, no difference was noted in the tendency to confront the task between participants in the control and attribute-affirmed conditions.